Do incentives matter when working for god? The impact of performance-based financing on faith-based healthcare in Uganda - Duchoslav, Jan; Cecchi, Francesco (Elsevier, 2019)
Can extrinsic incentives motivate faith-based healthcare providers? This paper challenges the finding that religious providers are intrinsically motivated to serve (poor) patients, and that extrinsic incentives may crowd-out such motivation. We use a unique panel of output and expenditure data from small faith-based nonprofit healthcare facilities in Uganda to estimate the effect of introducing performance-based financing. The output of the observed facilities is less than 50% of their potential. Performance-based financing increases output and efficiency robustly by at least 27%, with no apparent reduction in the perceived quality of services. Religious nonprofit healthcare providers may well be intrinsically motivated, but respond positively to extrinsic incentives. Whether working for god or not, incentives matter.